Transmission of Place Branding Values through Experiential Events: Wine BC Case Study - Cristofol, F. J.; Cruz-Ruiz, Elena de los Reyes; Zamarreño-Aramendia, Gorka (MPDI, 2021)
Sustainability is to promote economic growth that generates equitable wealth for all without harming the environment, becoming one of the objectives that serve as a starting point for many place branding strategies. Cultural heritage, environmental sustainability, and the valorization of the territory are nowadays unavoidable elements to sustain brands. This research analyzes the transmission of place branding values through experiential events, as a formula for business improvement according to the principles of sustainable development. The research is focused on the case of wine in British Columbia (Canada). The methodology applied was based on a theoretical framework as a starting point for the study. From there, on the one hand, an analysis of the contents of the events carried out by the winegrowers of British Columbia during the harvest months in 2019 and 2020 has been carried out. On the other hand, interviews were conducted with relevant professionals and academics in the sector in order to determine the extent to which they meet the needs of promotion of the site, taking into account the impact on the sustainability of the territory. The results show the link between the events and the territory brand, which is a means to generate growth through wine tourism promoted by the wineries, thus revaluing the winegrowing landscape and, in general, the traditions of the place, among others. There is also a need to look for strategies that seek collaboration between the public and private sectors to improve the creation of integrated events that transmit the branding values of the place. Events are a tool to generate territory branding and can, if well-conceived, contribute to the sustainable development goals (SDGs). In the case study, the results show that the vast majority of events organized by BC wineries aim to promote place branding within the framework of sustainability. A methodology that could be applicable to other territories and countries.
Keywords: Turismo; Vino; Marcas registradas; Desarrollo sostenible; Place branding; Wine tourism; Events management; Sustainable development; Cultural diplomacy